Students’ Perception on the Implementation of Online Learning in Kubutambahan District by Using Input and Outcome Evaluation - Gede Suadnya Suastika (LPPM Universitas Negeri Jakarta, 2022)
Covid-19 makes big problems especially in education. Students have an important role in education especially in online learning because they follow the online learning provided by the teacher. Based on the observation, students are afraid and embarrassed because of less attention from the students in online learning. This research aims to identify the students’ perception on the implementation of online learning in Kubutambahan District by using input and outcome evaluation, so that students can tell their problems in the online learning process. This research is descriptive qualitative which uses observation, questionnaire, and interview as data collection instruments. Input and outcome evaluation are the guidelines in designing the questionnaire and interview. The research results show that the students stated that assessment and schools’ facilities and infrastructures in SMPN 2 Kubutambahan and SMPN 5 Kubutambahan support them on the implementation of online learning although most of them have never followed socialization.